REVIEW : PENGARUH KONSELING APOTEKER TERHADAP KEPATUHAN TERAPI PASIEN HIPERTENSI DI BEBERAPA RUMAH SAKIT DI INDONESIA - Anggraini, Villia; Wahyuningsih, Sri (Jurnal Buana Farma, 2025)
Hypertension is one of the chronic diseases that requires long-term treatment. Adherence to medication is key to controlling hypertension. Pharmacist counseling can play an important role in improving patient adherence to medication. This study aims to analyze the influence of pharmacist counseling on therapy adherence and therapy outcomes in hypertensive patients through a literature review. The method used is a literature review approach. The literature search was conducted through Google Scholar and PubMed with a publication year range of 2014-2024. The selected articles must meet the inclusion and exclusion criteria. Out of the 424 articles found, 10 articles were selected for further analysis. The analysis results show that pharmacist counseling improves patient adherence to hypertension treatment. Studies show that counseling can lower patients' blood pressure, increase their knowledge, and improve their behavior during therapy. The effectiveness of counseling is also influenced by the patient's education. Pharmacist counseling helps lower blood pressure and improve adherence in hypertensive patients. Therefore, in the treatment of hypertension, pharmacist counseling should be used to improve the quality of life of patients and reduce the risk of hypertension complications.